Le Fléau Social. - Internationale Homosexuelle Révolutionnaire (IHR) (Paris : IHR, 1972)
Fonds Suzan Daniel (FSD)
Periodiciteit : driemaandelijks
Redactie : BP 252 16, 75766 Paris cedex 16
Frans
Krant